Brillouin scattering studies of ordered Pb(Sc1/2Nb1/2)O3 crystal with vacancies. (17th February 2020) - Kojima, Seiji; Hidaka, Yuuki; Tsukada, Shinya; Bing, Yonghong; Ye, Zuo-Guang
Abstract: Pb(Sc1/2 Nb1/2 )O3 (PSN) with a perovskite structure is a well-known ferroelectric material. The rapidly quenched PSN (PSN-D) shows a B-site disordered structure, and exhibits the noncanonical relaxor behavior with T max =around 351 K. The well-annealed PSN (PSN-O) exhibits a B-site 1:1 ordered structure, and undergoes a normal ferroelectric phase transition at T C = about 346 K, while, the introduction of vacancies may lead to the broadening of dielectric peak with frequency dispersion down to low temperatures, typical of relaxor nature. It was reported that as-sintered ordered PSN (PSN-OV) with Pb/oxygen vacancies exhibits relaxor ferroelectric behavior with T C = about 292 K. In this work, the elastic anomaly of a longitudinal acoustic (LA) mode and the central peak of a PSN-OV crystal were studied by Brillouin scattering. The temperature dependences of the frequency shift and the width of the LA mode along the [100] direction were investigated. A broad elastic anomaly and a broad slowing down of the relaxation time were observed at the ferroelectric phase transition. The elastic anomaly of PSN-OV is compared with those of PSN-D and PSN-O crystals reported in our previous studies. It is found that the relaxor nature of PSN-OV caused by vacancies is stronger than that of PSN-D caused by the B-site disorder.